If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = x + -19 Reorder the terms: y = -19 + x Solving y = -19 + x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -19 + x
| 5p-6(3p-10)=3p+6 | | m-5=13 | | (10-8i)(2-3i)= | | 6x^2+19x-77=0 | | 2h-9h+5h= | | 3x+5=4-(4x-4) | | 5.9-10= | | (2.14+15)0.33=2*2.14-1 | | 3(2)-2(3)+5(2)=p | | -4.9x^2+20x-15=0 | | 3(2)-2(3)+5(2)= | | 7.2=0.36n | | A=(y+5)(y-2)-6(y+5) | | 16=y+20 | | 5n+4-8n=-10 | | -4.0x+2.7-1.6x=-4.6+2.7 | | 4p-11p= | | (3.6+15)0.33=2*3.6-1 | | 2(2n+1)=4n | | 9x-2=16+2 | | (2.16+15)0.33=2*2.16-1 | | 8-3*(1p-4)=2p | | (0.35+15)0.33=2*0.35-1 | | -5c-6c= | | (-10)+(-7)=x | | 3x+5=6x-14 | | x(3x-1)=30 | | 15o=210 | | W+4=-10 | | (0.27+15)0.33=2*0.27-1 | | 0.3=15*x | | 37v^2-49t^2= |